1986
DOI: 10.1037/0033-295x.93.4.391
|View full text |Cite
|
Sign up to set email alerts
|

An efferent component in the visual perception of direction and extent.

Abstract: After outlining the history of motor theories of visual perception, a new theory linking information extraction patterns, specifically adapted for the guidance of eye movements, to the visual perception of direction and extent is presented. Following a brief discussion of comparative and physiological considerations, a research strategy to test for efferent involvement in visual perception in humans is presented. In seven demonstration experiments, predictions from efferent considerations are used to create a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 52 publications
(64 reference statements)
1
40
0
Order By: Relevance
“…The Müller-Lyer illusion generally increases monotonically as the angle becomes more acute (as long as the shaft lines are not too long), whereas the strength of the Ponzo illusion first increases, then decreases with the angle. Finally, Coren (1986) has shown that it is not the angle between the shaft and the arrowheads that is critical, but how far from the shaft the arrowheads extend. Longer arrowheads and more acute angles are equivalent in their effect on the Müller-Lyer illusion.…”
Section: Resultsmentioning
confidence: 99%
“…The Müller-Lyer illusion generally increases monotonically as the angle becomes more acute (as long as the shaft lines are not too long), whereas the strength of the Ponzo illusion first increases, then decreases with the angle. Finally, Coren (1986) has shown that it is not the angle between the shaft and the arrowheads that is critical, but how far from the shaft the arrowheads extend. Longer arrowheads and more acute angles are equivalent in their effect on the Müller-Lyer illusion.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should also be noted that reafference from motor commands appears to provide information about eye movements, leaving open the possibility of a contribution of the movement system (Helmholtz, 1867(Helmholtz, /1962). Coren's (1986) work also demonstrates that even readiness for eye movemeqts can have a substantial effect on visual perception, vendical or illusory. (For a review of the relation of eye movements to visual localization, see Matin, 1986.…”
Section: Discussionmentioning
confidence: 99%
“…Coren (1986), for example, showed that saccadic eye movements are responsible for the Mueller-Lyer optical illusion. The present experiments offered evidence that action can also influence the imagination.…”
Section: Discussionmentioning
confidence: 99%